Pengaruh Penggunaan Metode Show and Tell Terhadap Keterampilan Berbicara Bahasa Indonesia Siswa Kelas II SDN 183 Rabu Kabupaten Enrekang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Show and Tell method on the speaking skills of second-grade students at SDN 183 Rabu, Enrekang Regency. This research employed a quantitative experimental approach using a one-group pretest-posttest design. The sample consisted of 10 students. Data were collected through speaking performance tests and analyzed using descriptive and inferential statistics. The results showed a significant improvement in students’ speaking skills after the implementation of the Show and Tell method. In the pretest, most students were in the low and moderate categories, while in the posttest all students reached the high and very high categories. This indicates that the Show and Tell method has a significant positive effect on improving students’ speaking skills. Therefore, this method can be used as an effective and engaging learning strategy in elementary school language learning.